Gender Differences in Healthy Lifestyle Behaviours: A Case of Students at the Institute of Rural Development Planning in Dodoma, Tanzania - James, Stephen; Mwembezi, Gasper; Chusi, Tafuteni (European Journal of Health Sciences, 2022)
Purpose: Healthy lifestyle behaviours lead to good health and reduce the mortality rate. The objective of this study was to examine gender differences in healthy lifestyle behaviours among students at the Institute of Rural Development Planning in Dodoma, Tanzania. Methodology: The study area was Mbwanga ward at the respective Institute. The research design was cross-sectional in which data were collected from the population at a single point in time. The sample size was 160 respondents involving 67(41.9%) males and 93(58.1%) females out of 281 registered students in the Second Year Bachelor Degree Programme of Human Resource Planning and Management 2020/2021 academic year. The data collection method was interview while a structured self-reported questionnaire derived from the Lifestyle Screening Tool developed by Kim and Kang was a data collection tool. Descriptive and inferential statistics were used to conduct data analysis by Statistical Package for Social Sciences. Findings: Results showed that there were gender differences in healthy lifestyle behaviours. Females were at least leading in perceiving desirable behaviours which included water drinking, air-breathing, dietary habits, temperance and trust. Males only did better on two healthy lifestyle behaviours which included sleep and physical exercise compared with females. Further results on the Independent Samples t-Test (t [158] = -1.858; p showed that even though both gender had different perceptions of their lifestyle behaviours, such difference was not statistically significant. Recommendations: The study recommended that students' Programme Coordinators should remind students to drink sufficient water for keeping good health on occasions of their scheduled meeting; while students should plant more trees and flowers at the Campus and in residential areas to optimize clean air-breathing.